X-(5-x)/3=1

Simple and best practice solution for X-(5-x)/3=1 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for X-(5-x)/3=1 equation:



X-(5-X)/3=1
We move all terms to the left:
X-(5-X)/3-(1)=0
We add all the numbers together, and all the variables
X-(-1X+5)/3-1=0
We multiply all the terms by the denominator
X*3-(-1X+5)-1*3=0
We add all the numbers together, and all the variables
X*3-(-1X+5)-3=0
Wy multiply elements
3X-(-1X+5)-3=0
We get rid of parentheses
3X+1X-5-3=0
We add all the numbers together, and all the variables
4X-8=0
We move all terms containing X to the left, all other terms to the right
4X=8
X=8/4
X=2

See similar equations:

| (5-1)^x=64 | | 8m+10=-86-4m | | 5x-6=-x-129 | | 4t*5t=6t | | x(x-17)-18x=(x-3)+(x+16) | | (2x-14)=(2x+19) | | (2x+19)=(2x-14) | | v+-62=37 | | f-19=-12 | | 6(g+3)+6=2g-4 | | 2s=10,s= | | 3n+3-5(n-1)=16. | | 7x+39=67 | | (2x-25)=87 | | 63g-39g-7g-12g-2g=15 | | 14n-(-43n)+(-55n)-(-12)=-60 | | 25r-65r-61r+99r+49=-17 | | -67j+21j-(-85j)-26j=91 | | 33g-13g+8g+8g+10g+10=56 | | -40n-(-4n)+92n=-56 | | 81y-70y-(-92)=-84 | | -13a-(-9a)-8=16 | | 45m-(-45m)+(-26m)-(-30)=-34 | | (X+3)2^+(y-4)2^=36 | | x+(x+1)+(x-1)=195 | | 25n-38n+(-13)=26 | | (x+1)+(x-1)=195 | | 21c+40c-(-42c)-32c+(-22c)=49 | | 6u-9u=6(2)+u | | 16z+(-14z)+11z-(-3z)=-16 | | 18v+12v-7v-15v+(-7v)-(-7)=-13 | | 10v-3v+v+v=9 |

Equations solver categories